2018
DOI: 10.1177/1420326x18793997
|View full text |Cite
|
Sign up to set email alerts
|

The on-board carbon dioxide concentrations and ventilation performance in passenger cabins of US domestic flights

Abstract: Billions of people travel on airplanes every year, making the aircraft cabin a critical environment to understand with regard to public health. The main control over indoor environmental quality in the cabin is ventilation; therefore, maintaining sufficient ventilation rates on-board is essential for creating healthy and comfortable cabin environments. We measured real-time CO2 concentrations, an indicator of ventilation rates, and cabin pressure in the passenger cabins of 179 US domestic flights from boarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…The flight deck has been under studied, however; nearly all of the research to date on these environmental factors in airplanes, has focused on conditions in the airplane cabin [25,26,27,28,29]. Specific to air quality, a focus of our current study, one study of 179 U.S. domestic flights, Cao et al [30] found an average CO 2 concentration of 1353 ± 290 ppm (mean ± SD) during all flight phases, but as high as nearly 3000 ppm during boarding, a time when the flight deck door is usually open. The equivalent outside air ventilation rates could only meet the minimum value of 4.7 L/s/p as required by Federal Aviation Regulations [31] 42% of time during boarding and 73% of time during flying.…”
Section: Introductionmentioning
confidence: 99%
“…The flight deck has been under studied, however; nearly all of the research to date on these environmental factors in airplanes, has focused on conditions in the airplane cabin [25,26,27,28,29]. Specific to air quality, a focus of our current study, one study of 179 U.S. domestic flights, Cao et al [30] found an average CO 2 concentration of 1353 ± 290 ppm (mean ± SD) during all flight phases, but as high as nearly 3000 ppm during boarding, a time when the flight deck door is usually open. The equivalent outside air ventilation rates could only meet the minimum value of 4.7 L/s/p as required by Federal Aviation Regulations [31] 42% of time during boarding and 73% of time during flying.…”
Section: Introductionmentioning
confidence: 99%
“…The internal density of the cabin is high, which causes the cabin environment to be complex and have many influencing factors (Bosbach and Dehne 2016). Mixing ventilation (MV) systems were widely used in commercial aircraft (Cao et al 2019). Once one of the passengers was infected by a virus, the gaseous pollutants will quickly spread through the airflow and be transported to other passengers in the aircraft cabin.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, studies on thermal comfort in weightlessness is important to the conservation of the astronauts' performance and is also useful in the environmental improvement of the aircraft for the domestic flight. 7,8 Unfortunately, very few studies on thermal comfort under weightlessness have been reported. Instead, most studies have been focusing on the thermoregulation of the human body during exposure to weightlessness, without considering the significance of the effect on the thermal comfort, since the thermoregulation is about the survival of astronauts and thus is thought to be more important.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, studies on thermal comfort in weightlessness is important to the conservation of the astronauts’ performance and is also useful in the environmental improvement of the aircraft for the domestic flight. 7,8…”
Section: Introductionmentioning
confidence: 99%